Contextualization Of Hadith By Syuhudi Ismail As A Method Of Understanding Contemporary Hadith - Raadliyatush Shalihah; Muhammad Habibi Hamzah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The study of the understanding or matan of hadith has become the focus of study of contemporary scholars after the discontinuity of transmission and the absence of new transmission. Unlike the classical scholars who focused on the study of the hadith, contemporary scholars discuss the meaning or content of the hadith because this is considered important to be understood and then practiced by Muslims. In the study of the meaning of hadith, many contemporary scholars contextualize hadith to bring the meaning of hadith closer to the current context. One of the Indonesian scholars of hadith who contextualized hadith is Syuhudi Ismail through his book Textual and Contextual Hadith of the Prophet by characterizing some of the traditions listed as temporal, universal and local traditions after analyzing the asbabul wurud and the existence of the 'illat of the hadith. This research uses a qualitative method, literature review by making the book by Syuhudi Ismail as the primary source and other scientific articles as secondary sources.